2022
DOI: 10.1108/ijotb-10-2020-0175
|View full text |Cite
|
Sign up to set email alerts
|

“Can politics really be beneficial?” Toward a model for positive politics through consensus

Abstract: PurposeThis article wants to propose deeper insights and clarifications into the effects of organizational politics which have been at the center of many debates in decision-making literature. For a long time, the debate focused on the negative effects of organizational politics and how to avoid them. This article wants to explore the positive effects of organizational politics and see how this impacts the consensus process in teams moderated by organizational change.Design/methodology/approachThe article mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 101 publications
(157 reference statements)
0
2
0
Order By: Relevance
“…Although research has recently reported that organizational politics has a positive impact on organizations (Parmentier and Reynaud, 2022), organizational politics is still recognized by many researchers as a factor that has a negative impact on organizations and their members. The meta-analysis studies by Chang et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although research has recently reported that organizational politics has a positive impact on organizations (Parmentier and Reynaud, 2022), organizational politics is still recognized by many researchers as a factor that has a negative impact on organizations and their members. The meta-analysis studies by Chang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Although research has recently reported that organizational politics has a positive impact on organizations (Parmentier and Reynaud, 2022), organizational politics is still recognized by many researchers as a factor that has a negative impact on organizations and their members. The meta-analysis studies by Chang et al (2009) and Miller et al (2008) presented that the perceptions of organizational politics increased negative outcomes such as employees' intention to turnover, higher stress, and job tension.…”
Section: Introductionmentioning
confidence: 99%